2018
DOI: 10.1002/biot.201700598
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR–Mediated Genome Editing and Gene Repression in Scheffersomyces stipitis

Abstract: Scheffersomyces stipitis, renowned for its native xylose-utilizing capacity, has recently demonstrated its potential in producing health-promoting shikimate pathway derivatives. However, its broader application is hampered by the low transformation efficiency and the lack of genetic engineering tools to enable sophisticated genomic manipulations. S. stipitis employs the predominant non-homologous end joining (NHEJ) mechanism for repairing DNA double-strand breaks (DSB), which is less desired due to its incompe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 25 publications
0
40
0
Order By: Relevance
“…Native DNA repair types and efficiency also largely determined genome editing rate, because DSB induced by CRISPR/Cas9 can be repaired by NHEJ, resulting in indels and gene inactivation, or be repaired by HDR, resulting in precise genome editing by supplying proper DNA donors. Thus, in some organisms with both NHEJ and HDR pathways, deletion of KU70 / KU80 often repressed NHEJ and increased CRISPR mediate genome editing rate through HDR ( Gao S. et al, 2016 ; Schwartz et al, 2016 ; Cao et al, 2018 ; Bae et al, 2020 ). However, in some organisms lacking HDR, phage-derived recombinases (RecET and λ-Red) should be co-expressed with Cas9, similar to the approaches adopted in E. coli ( Jiang et al, 2015 ; Wang B. et al, 2018 ).…”
Section: The Crispr/cas System For Genome Editingmentioning
confidence: 99%
“…Native DNA repair types and efficiency also largely determined genome editing rate, because DSB induced by CRISPR/Cas9 can be repaired by NHEJ, resulting in indels and gene inactivation, or be repaired by HDR, resulting in precise genome editing by supplying proper DNA donors. Thus, in some organisms with both NHEJ and HDR pathways, deletion of KU70 / KU80 often repressed NHEJ and increased CRISPR mediate genome editing rate through HDR ( Gao S. et al, 2016 ; Schwartz et al, 2016 ; Cao et al, 2018 ; Bae et al, 2020 ). However, in some organisms lacking HDR, phage-derived recombinases (RecET and λ-Red) should be co-expressed with Cas9, similar to the approaches adopted in E. coli ( Jiang et al, 2015 ; Wang B. et al, 2018 ).…”
Section: The Crispr/cas System For Genome Editingmentioning
confidence: 99%
“…The NHEJ-knockout strategy has been more extensively explored and is generally successful in the organisms in which it has been attempted, although it typically results in much weaker DNA repair overall as the residual HR pathway of the organism is not as efficient. [38][39][40][41] Overexpression of RAD51 has been less explored, but it has been shown to increase the rates of HR in mammalian cells, while also resulting in greater chromosomal instability. 42,43 In Codon optimization of Cas9 can prove essential, particularly in microorganisms with a strong codon bias such as R. toruloides or Streptomyces species.…”
Section: Promoters and Terminatorsmentioning
confidence: 99%
“…Deactivated Cas9 harboring the D10A and H841A mutations was fused with the mammalian repression domain Mxi1, enabling up to 32% repression of GFP. 40 An ARS allowing plasmid maintenance in S. stipitis, ARS2, was first identified in 1994 by Yang et al, 75 NHEJ has been reported to be the dominant DNA repair pathway in S. stipitis. In the wild-type background, HR-based DNA integration is reported to occur in 1% of transformants 76 for KU80 disruption.…”
Section: Schefferosomyces Stipitismentioning
confidence: 99%
See 1 more Smart Citation
“…Gao et al also demonstrate a new technology for the host Y. lipolytica by established a method for facile gene excision and targeted integration using a dual CRISPR‐Cas9 cleavage approach using paired sgRNAs . Finally, Cao et al explore CRISPR approaches in an alternative, non‐conventional host S. stipitis and develop a ku70Δku80Δ deletion strain as well as establish methods for gene repression in this promising biofuels host …”
mentioning
confidence: 99%